2019
DOI: 10.3390/su11174634
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Scale and Scope of Workplace Bullying: An Alternative Workplace Bullying Scale

Abstract: The toll of workplace bullying is immense, yet, similarly as with an iceberg, its scope, scale and implications tend to remain underestimated. Several ways of assessing the prevalence of workplace bullying have been proposed in the literature. The most frequently discussed are the ‘subjective method’ assessing individuals’ perceptions of being a victim and the questionnaire, i.e., criterion-based, methods, including Negative Acts Questionnaire (NAQ) and Leymann Inventory of Psychological Terror (LIPT). Since i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…While workplace bullying has attracted the attention of researchers for some time, differences in defining and measuring it persist (for example, Lewis et al, 2008;Anjum et al, 2019). Anjum et al (2019) suggest a concise definition: "workplace bullying is essentially about purposeful breaches of an individual's space of dignity, rights, and integrity" (p. 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While workplace bullying has attracted the attention of researchers for some time, differences in defining and measuring it persist (for example, Lewis et al, 2008;Anjum et al, 2019). Anjum et al (2019) suggest a concise definition: "workplace bullying is essentially about purposeful breaches of an individual's space of dignity, rights, and integrity" (p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…While workplace bullying has attracted the attention of researchers for some time, differences in defining and measuring it persist (for example, Lewis et al, 2008;Anjum et al, 2019). Anjum et al (2019) suggest a concise definition: "workplace bullying is essentially about purposeful breaches of an individual's space of dignity, rights, and integrity" (p. 1). For behaviours to be considered bullying, they must occur regularly, occur over a prolonged period of time and arise from a power inequality between the victim and the bully (Anjum et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it cannot be known if the structure of the scale is equivalent for men and women and whether the item functioning is the same for both genders. Another limitation of our work is the implications of statistical techniques only, thus, in future studies, we further plan to employ state-of-the-art natural language processing and machine learning techniques to better understand the aversive effects of SAD on daily functioning; these have already proven to be highly useful in understanding other disorders that can lead to psychological problems, directly or indirectly [39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Limitationsmentioning
confidence: 99%
“…Balancing work-family demands has become an increasingly exigent task for working personnel around the globe [16]. Work to family interference (WIF) factors tend to be related with job type, job involvement, job flexibility, work time commitment [17], inflexible working hours or schedules [32], overtime [33], and workplace bullying [34] considered as responsible of causing occupational stress among the workers [35]. A research conducted with working women reported that women tend to have a poor relationship with their spouses as a result of inflexible work schedule [36] and unfinished work [37].…”
Section: Literature Review: Work Family Conflict and Its Diverse Facetsmentioning
confidence: 99%